EL ROL DE LA INTELIGENCIA ARTIFICIAL EN LA AUTORÍA DE ARTÍCULOS CIENTÍFICOS EN ODONTOLOGÍA: ENFOQUES ÉTICOS PARA UN USO RESPONSABLE - Arriola-Guillén, Luis Ernesto (2025)
A central challenge in contemporary dentistry is determining how to ethically and responsibly integrate artificial intelligence tools, such as ChatGPT, DeepSeek, and Google Gemini, into scientific article writing, review, and development, while ensuring that these technologies do not compromise researchers’ originality or fundamental responsibilities (1-4). The coming years will be critical for establishing clear boundaries. Although AI tools can support specific aspects of research, they should not be used to generate research ideas or to author scientific articles. These issues require us to clarify the distinct roles of researchers and establish effective strategies to safeguard the originality of our studies.